POLICY ANALYSIS ON LOCAL WISDOM TO STRENGTHEN NATIONAL IDENTITY THROUGH CITIZENSHIP COURSES IN HIGHER EDUCATION - Sudrajat, Tatang; Hadimin, Deni Nurdyana; Kurniasih, Wiwit; Rohayati, Yeti (Jurnal Progress Administrasi Publik, 2025)
Local wisdom in each region is very important in strengthening national identity. This is especially when associated with the challenges and problems of the nation in the current global era. Higher education institutions with their resources play a strategic role in strengthening this national identity. Decree of the Director General of Higher Education Number 84/E/KPT/2020 and several other state and government regulations are public policies related to this. This study aims to analyze the profile, context, and substance of government policies regarding Citizenship courses in relation to the existence of local wisdom to strengthen national identity.This study uses normative juridical methods, and literature studies, by examining the substance of government regulations and analyzing various relevant documents. The results of the study show that there are government regulations which are public policies related to local wisdom which are very important for strengthening national identity. The integration of local wisdom themes into Citizenship courses is very strategic so that students avoid being uprooted from the roots of the nation's culture. Government officials at the Ministry of Education, Culture, Research and Technology (Kemendikbudristek), university leaders, lecturers in charge of Citizenship courses, cultural activists and local wisdom, and other education stakeholders are policy actors. The threat of the erosion of identity as a nation among students is a policy issue. Kemendikbudristek, universities and institutions outside the government that care about the issue of strengthening national identity are policy institutions. The public's hope that students as part of the young generation with a strong national identity is the policy environment. There are several policy substances in government regulations that need to be improved. Keywords: Citizenship; Local Wisdom; Local Wisdom; Policy; Universities.